Traditional Chinese exercise for non-valvular atrial fibrillation: A protocol for systematic review and meta-analysis. Issue 49 (9th December 2022) - Wang, Te; Jin, Hongguang; Wang, Yiqiang; Liu, Meixi; Liu, Huan; Zhu, Xing; Guo, Wenping; Fan, Chunhui; Huang, Yongsheng; Jiang, Lihong
Abstract : Introduction: Traditional Chinese exercises have become an important part of cardiac rehabilitation. It can coordinate the essence, qi, and spirit of the human body, and has the functions of promoting joints, stretching muscles and bones, ventilating and blood circulation, so as to achieve the balance between hardness and softness, and between yin and yang. We hope that the research results based on systematic review and meta-analysis will provide a theoretical basis for the treatment of atrial fibrillation (AF) with traditional Chinese exercise. Methods: The systematic review will be performed according to the Cochrane Handbook for Systematic Reviews of Interventions. The protocol is being reported in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols Statement. An literature search strategy will be developed and adapted for 9 databases. Searches will be run from the database inception until the date of the search implementation and be updated before the review is completed. Meta analysis will be performed using Review Manager 5.3 and R packages. Conclusion: This protocol introduces a systematic review and meta-analysis of traditional Chinese exercises in the treatment of nonvalvular AF and will clarify the efficacy and safety of traditional Chinese exercises in the treatment of AF. This will further provide theoretical support for clinical treatment of AF.